Hydrogeographische Grundlagen der Bewässerungswirtschaft im Nigertal/Rep. Niger - Janke, Bernd (ERDKUNDE, 1976)
The discharge of the Niger, which flows through the western part of the Mali Republic as an exotic river, is subject to temporal as well as regional modifications;these are determined on the one hand by its headwaters and the inland delta of the Niger, and on the other by the inflow of its Sudanic tributaries. High discharge in the period September to April contrasts with the extremely low discharge in the summer months (May-August). Since the absence of dams prevents the storage of the winter discharge and its utilisation for all-the-year-round irrigation, this hydrological potential remains largely unused. Thus only those districts in the Niger Valley which are subject to natural fluctuations between high and low water-mark could seasonally be enhanced in value by irrigation in the form of controlled flooding. High discharge in the low relief of the northern section (Ansongo - southern Tillabery) leads to considerable expansion of the area covered by water, thereby creating generally good natural conditions for controlled irrigation by flooding, whereas it results in no more than a clear rise to higher water-levels in the relatively narrow, well defined valley in the section south of Tillabery to Malanville, only inundating the shallow slip-off slopes and abandoned stream channels. These are the only ones here which are naturally well suited to irrigation cultivation. Although there is a very varied and distinct regional differentiation in suitability as land for irrigation, due to the natural potential (especially in the mode of run-off, water-levels and valley relief) of this valley region, the Niger Valley as a whole must be considered an agricultural area of increasing importance in the Niger Republic.